Challenges Faced By Arab Students in Learning English: Exploring the challenges faced by Arab learners in acquiring English as a second language (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Present paper is a deep study of the challenges faced by Arab learners in learning English as a second language. The paper will explore the differences between English and their native language which makes learning English a strenuous job for them. The article also aims to particularly examine some contributing factors like dominance of their 1st language, some missing sounds in Arabic and the difference between the structure of their native language and English which again increase complications in their language acquisition.